Nitrogen fixation by indirect titration of ammonium ion of bacteria isolated from rhizosphere and caulosphere of maize plants (Zea mays L.) - Reyes-Nava , L. A.; Pliego-Sandoval , J. E.; Reyes-Bautista, Raúl; Iñiguez-Muñoz , L. E. (Rev. iberoam. bioecon. cambio clim., 2025)
Background: Mexico is one of the main producers, exporters and consumers of corn in the world. For maximum yield of the product, nitrogen fertilizers are supplied as the main source of nutrients. However, their excessive use is creating a contamination problem. Objective: The main objective was to isolate and select nitrogen-fixing bacteria from the rhizosphere and caulosphere of corn plants. Methodology: Corn plants were selected during three different periods: vegetative growth, flowering and fertilization, grain filling and maturity. Root and stem samples were obtained from each of the plants, they were superficially disinfected, serial dilutions were made and they were planted in nutrient agar medium for isolation. The nitrogen-fixing capacity was evaluated qualitatively on a nitrogen-free medium and quantitatively through the indirect ammonium ion titration method. Results: 70 bacterial isolates were obtained, of which 14 presented positive nitrogen-fixing activity in vitro. Only isolates RB14, RC12, CB1 and CC3 presented quantifiable ammonium ion concentrations, with values ​​of 1.081 mg/L, 0.546 mg/L, 0.54 mg/L and 0.163 mg/L of released ammonium, respectively. According to the macroscopic and microscopic characteristics observed, the microorganisms that presented nitrogen fixing capacity showed a morphological similarity to the genera Bacillus sp, Pseudomonas sp and Azotobacter sp. Conclusions: These isolates can be used as an alternative to the use of chemical fertilizers since they showed a high nitrogen fixation potential in vitro.